Pengembangan Keterampilan Berbahasa Lisan Anak Tunarungu Melalui Terapi Bermain di TK Masyitoh Talang Tegal - Anisatul Laely, Titi; Aerin , Wafa (ACIECE, 2019)
Currently, there are still children with special needs who have not received serious attention in educational institutions, especially Early Childhood Education. One of them is children with special needs who are deaf. Physically, usually children who have hearing loss like normal children. However, experiencing disruption in the auditory organs resulting in inability to hear, ranging from mild to severe levels are classified into deaf (deaf) and less with (hard of hearing). This study aims to describe the implementation of the development of oral language skills of deaf children through play therapy. The background of this research is the direct impact is the obstruction of verbal communication, both expressive (speaking) and receptive. These obstacles result in the education and learning process of deaf children. However, deaf children have the potential to learn to speak and speak. Therefore, deaf children need special services to develop language and speaking skills so as to minimize the impact of their disability. This research uses a qualitative approach with a phenomenological type. The population in this study is all children and parents in TK Masyitoh Talang Tegal. Data collection is done by observation, interviews, questionnaires, field notes, and documentation. Data analysis uses descriptive analysis techniques. This research shows that the language skills of deaf children can be improved through play therapy